Mechanism of Differential Natural Gas Enrichment on the Northern and Southern Sides of the Lingshui Sag, Qiongdongnan Basin - Yang, Haoyuan (Scientific Journal of Technology, 2026)
The natural gas enrichment in the Lingshui Sag of the Qiongdongnan Basin exhibits a prominent spatial pattern characterized as "superior in the south and inferior in the north, dry in the south and mixed in the north." This paper systematically compares the hydrocarbon accumulation conditions on the northern and southern sides to elucidate the mechanisms driving this differential enrichment. Research indicates that the coal-measure source rocks of the Yacheng Formation on the southern side possess tremendous hydrocarbon generation potential. Furthermore, the deep-water gravity flow channel sandstone reservoirs of the Huangliu Formation are large in scale and feature excellent physical properties. Coupled with the development of a highly efficient three-dimensional vertical transport system composed of mud diapirs and associated faults, the southern side possesses a superior foundation for hydrocarbon accumulation. In contrast, the northern side is constrained by multiple unfavorable factors, including low organic matter abundance in source rocks, thin and poor-quality submarine fan reservoirs, weak fault transport connectivity, and a high susceptibility to dispersion, which ultimately limits the scale of natural gas accumulation. The spatial configuration differences in various geological factors—namely generation, storage, and transportation—directly determine the accumulation efficiency and scale of natural gas in this region.